Extraction, Purification And Characterization Of Artocarpus Altilis Latex Protease As A Fibrino(Geno)lytic Agent - Zulfigar, Siti Balqis (2019)
The harvesting of Artocarpus altilis (breadfruit) in plantations involves the process of draining the latex to avoid staining of the epicarp. The exudate is not fully utilized and it has no commercial value. Ethnopharmacological applications of the latex in wound healing imply its action on blood coagulation and fibrinolysis. Partial purification of A. altilis latex through HiTrapTM SP Sepharose chromatography had purified a 72 kDa protease by 3.1-fold with 24% recovery and the specific activity of 4.87 U/mg. This serine protease was inhibited by phenylmethanesulfonyl fluoride (PMSF) (1 mM and 10 mM) with 89% and 27% of residual activities respectively. The protease showed maximal activity at pH 10 with casein and bovine serum albumin (BSA) as substrates. The protease’s apparent optimal temperature after 30 minutes of incubation was 80C. The Km and Vmax values on casein were 0.453 ± 0.026 mM and 0.022 ± 0.001 μmol/min, respectively. The protease was stable at a broad pH range (pH 4-11) with no significant reductions were detected after 24h. Thermodynamic parameters like the enthalpy (ΔH), free energy change (ΔG) and entropy (ΔS) of the protease’s inactivation at the temperature of 55-75C were estimated to be in the range of 80.10-80.27 kJ/mol, 108.34-109.32 kJ/mol and 83.97-85.58 J/mol respectively. The energy of inactivation (Ed) was 82.9 kJ/mol. A. altilis protease (0.125 U) had a comparable fibrinogen clotting capacity with thrombin (0.25 U) during the first 75 min of incubation.